CROSS-CULTURAL COMMUNICATION BETWEEN LOCAL AND NON-LOCAL PLAYERS ON THE CIREBON UNITED SOCCER TEAM - Radja Djibrali; Farida Nurfalah; Dedet Erawati (Bulletin of Engineering Science, Technology and Industry, 2026)
The diversity of cultural backgrounds within a multicultural soccer team has the potential to influence communication patterns, cohesion, and the effectiveness of cooperation among players. This study aims to analyze the dynamics of intercultural communication within the cirebon united soccer team composed of players native to cirebon united and players from outside the region using the cultural inteligence (CQ) framework. This study employs a qualitative case study approach, utilizing participatory observation and in depth interviews with local players, players from outisde the region, and the coach. Data were analyzed thematically based on the four dimensions of CQ: metacognitive, cognitive, motivational, and behavioral. The results indicate that differences in regional language and accents during the initial stages of interaction have the potential to cause misunderstandings, however, these did not escalate into conflicts because they were managed through clarification of meaning, the use of indonesian as a common language in formal contexts, and the strengthening of informal interactions that fostered emotional closenes. The four dimensions of CQ operate simultaneously during training, matches, and social interactions, thereby forming adaptive communication patterns that support team cohesion and performance stability. This study contributes to the fields of sports communication by demonstrating that cultural inteligence functions not only as an individual competency but also as an integrative mechanism that shapes the effectiveness of collective communication within a multicultural regional level soccer team.